ANGKA KEJADIAN TUBERKULOSIS PARU PADA PASANGAN SUAMI-ISTRI PNEDERITA TUBERKULOSIS PARU BTA POSITIF DI POLIKLINIK PARU RSUD ARIFIN ACHMAD - Diadema Al Arif,; Zarfiardy Aksa Fauzi; Fauzia Andrini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
AbstractPulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Mycobacterium tuberculosis is carried in airborne particles, called droplet nuclei. Tuberculosis infection is spread from a person ti person by inhaling the droplets of infected material produced by a person with infectious pulmonary tuberculosis, patients with positive Acid Fast Bacilli (AFB) smear. Droplet nuclei can survive in the air for several hours depend on enviromental factor, source case or person with active tuberculosis and contact or person who is exposed to infectious pulmonary tuberculosis patients. Home is vulnerable place for transmission this disease to its contacts. Family such as spouse, children and parents have a higher risk to be transmitted. This was a descriptive study to know prevalence of pulmonary tuberculosis in spouse of pulmonary tuberculosis patients with positive Acid Fast Bacilli (AFB) smear in Arifin Achmad General Hospital. The samples of this study are 30 people. Results showed that 1 samples (3,33%) had a positive Acid Fast Bacilli (AFB) smear and abnormal radiographKeyword : tuberculosis,transmission,spouse